Migrant associations as alternative jobs providers: Experience of Turkish and sub-Saharan communities in Belgium - Manco, Altay; Gerstnerova, Andrea (Border Crossing, 2016)
It can be said that Belgian labour market has been challenged since the 1970s due to changing economic landscape. The two major drivers for change were the deindustrialization and globalization. For some, these two drivers have brought a perceptible deterioration of working conditions and pay. In general, foreign workers are among the first to be affected from such changes. Their temporary residence status, unrecognized qualifications, limited language skills and lack of access to the social networks of the native-born Belgians make them particularly disadvantaged in the labour market. In order to overcome these obstacles, migrant communities have developed various, more or less effective, measures. This paper discusses the role of migrant associations in economic integration among the Turkish and the sub-Saharan communities residing in Belgium. Particular emphasis is made on the contribution of the community’s social capital in the process of transferring knowledge, financial and material means and professional networks.